ERROR ANALYSIS OF SIMPLE PRESENT TENSE USE IN DESCRIPTIVE TEXT WRITING AT SMA SWASTA MASEHI GBKP BERASTAGI - Purba, Twinta; Sinaga, Elisabeth Ruthana Lasmaria; Lubis, Frida Dian Handini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to identify, classify, and describe the types and patterns of errors in the use of the simple present tense in descriptive texts written by tenth-grade students at SMA Swasta Masehi GBKP Berastagi, along with the underlying causes. A qualitative descriptive design was employed. Thirty students participated by writing descriptive paragraphs about a person and completing a questionnaire. Error analysis based on James and Tono's taxonomy revealed that omission errors, particularly the absence of the